Influence of Berry Heterogeneity on Phenolics and Antioxidant Activity of Grapes and Wines: A Primary Study of the New Winegrape Cultivar Meili (Vitis vinifera L.). - Xu Liu; Jinlu Li; Yuping Tian; Mingan Liao; Zhenwen Zhang (PLoS ONE)
Wine grapes are usually harvested in vineyards when they ripen. However, not all of the berries in a vineyard ripen homogeneously because of different microclimates around the clusters and berries. In this study, the influence of berry heterogeneity on the phenolic content and antioxidant capacity of grapes and wines under a continental monsoon climate was evaluated for a new wine grape cultivar Meili (Vitis vinifera L.). The total phenolic, flavonoid, flavanol, and monomeric anthocyanin contents in the skin and wine significantly increased with grape density; however, there was no significant difference in the seeds between the two lower densities. The highest values of DPPH free radical-scavenging activity, cupric-reducing antioxidant capacity, and hydroxyl radical-scavenging activity in the skin, seed and wine were detected for the densest berries. The sum of individual phenolic compounds in skin, seed and wine increased with berry density, though no significant difference for skin was observed between the two higher density classes. Hence, the chemical components of Meili grapes and wines were positively associated with the berry density at harvest under the continental monsoon climate.